Anaerobic digestion of pulp and paper mill sludge pretreated by microbial consortium OEM1 with simultaneous degradation of lignocellulose and chlorophenols. (August 2017) - Lin, Yunqin; Liang, Jiajin; Zeng, Chao; Wang, Dehan; Lin, Huanjia
Abstract: This work focused on the anaerobic digestion performance of pulp and paper mill sludge (PPMS) pretreated with the microbial consortium OEM1, and exposing the mechanism of performance variations as well. It was found that the methane yield was increased 1.4-fold by pretreating feedstocks with the active OEM1, and the maximum methane yield of 429.19 mL/gVS was noted. Moreover, an appropriate pH range of 6.1–7.5 was found in this digester, and no VFA inhibition was observed. A higher level of stability was also detected in this system based on the analysis of ORP, alkalinity and VFA/TA ratio. Also, a higher lignin decomposition rate was determined in the coupled pretreatment - AD process with the active OEM1 addition, and a 5-fold increase of AOX degradation efficiency was found in the pretreatment stage. Hence, a brighter future of developing OEM1 pretreatment for PPMS before AD could be predicted based on the capabilities of selective delignification and effective AOX degradation. Graphical abstract: Highlights: Pretreating PPMS with OEM1 for lignocellulose deconstruction and AOX detoxification. Selective lignin-degradation ability of the OEM1 was noted. A 5-fold increase of AOX degradation was gained with active OEM1 pretreatment. AD performance was improved by adding feedstocks pretreated with active OEM1.